Perencanaan Revetment pada Sebelah Timur Pantai Kuala Jangka Kecamatan Jangka Kabupaten Bireuen - Fahmi, Mirza (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Almuslim, 2023)
Kuala Jangka Beach is one of the beaches in the village of Jangka Alue, Term District, Bireuen Regency, Aceh Province. Which is a tourist spot and also a fishery area for fishermen. Waves that are high enough to impact the shoreline so that some areas are eroded due to erosion. Therefore, a coastal protection structure is needed, namely a revetment. A revetment is a coastal protection structure that functions to protect the beach from scouring waves to minimize erosion around the coast. The data used in this planning are wind data, bathymetry, and tidal data. Based on the results of the analysis it is known that the dominant wind that occurs is from the east which is equal to 36%, with the greatest speed being 10 knots or 8.65 m/s. The design wave height calculated from the prevailing wind characteristics is 1,699 m. Sedimentation analysis shows that sedimentation at Kuala Term Beach is dominated by longshore sediment transport which reaches 1,360,132.805 m3/year. Revetment construction is calculated using the general revetment planning formula. The revetment was built from the mountain rock. The height of the revetment building is 3 m with a peak width of 1.5 m and the thickness of the revetment guard wall is 1.5 m and the weight of the bag as a protective layer is 0.301 tons. Meanwhile, the height of gaiters for revetment buildings is 0.75 m with a width of 2.5 m.